2022
DOI: 10.1007/s12325-022-02231-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone Furoate/Umeclidinium/Vilanterol (FF/UMEC/VI) Triple Therapy Compared with Other Therapies for the Treatment of COPD: A Network Meta-Analysis

Abstract: Introduction: Randomized controlled trials (RCTs) comparing triple therapies (inhaled corticosteroid [ICS], long-acting b 2 -agonist [LABA], and long-acting muscarinic antagonist [LAMA]) for the treatment of chronic obstructive pulmonary disease (COPD) are limited. This network meta-analysis (NMA) investigated the comparative efficacy of single-inhaler fluticasone furoate/umeclidinium/vilanterol (FF/ UMEC/VI) versus any triple (ICS/LABA/LAMA) combinations and dual therapies in patients with COPD. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 40 publications
(52 reference statements)
1
26
1
Order By: Relevance
“…However, the random-effects model, as recommended per best practice, showed no significant treatment-effect differences, due to wide CIs driven by between-study heterogeneity. Given the methodological issues, selective reporting of fixed-effects model results, and failure to disclose the random-effects model results, which we believe to be not significant per our replicate analysis, we do not agree with Ismaila et al that FF/UMEC/VI showed statistically significant improvements in annualized moderate/severe exacerbation rates versus budesonide/glycopyrronium bromide/formoterol fumarate (BUD/GLY/FOR) [1]. Notably, their finding contradicts four other peer-reviewed NMA publications, including two from independent researchers [8,9], all of which used random-effects models to account for heterogeneity and reported no significant exacerbation rate differences between triple therapies in patients with chronic obstructive pulmonary disease [8][9][10][11].…”
Section: Dear Editorcontrasting
confidence: 81%
See 3 more Smart Citations
“…However, the random-effects model, as recommended per best practice, showed no significant treatment-effect differences, due to wide CIs driven by between-study heterogeneity. Given the methodological issues, selective reporting of fixed-effects model results, and failure to disclose the random-effects model results, which we believe to be not significant per our replicate analysis, we do not agree with Ismaila et al that FF/UMEC/VI showed statistically significant improvements in annualized moderate/severe exacerbation rates versus budesonide/glycopyrronium bromide/formoterol fumarate (BUD/GLY/FOR) [1]. Notably, their finding contradicts four other peer-reviewed NMA publications, including two from independent researchers [8,9], all of which used random-effects models to account for heterogeneity and reported no significant exacerbation rate differences between triple therapies in patients with chronic obstructive pulmonary disease [8][9][10][11].…”
Section: Dear Editorcontrasting
confidence: 81%
“…We read with interest the publication by Ismaila et al in Advances in Therapy entitled ''Fluticasone Furoate/Umeclidinium/Vilanterol (FF/ UMEC/VI) Triple Therapy Compared with Other Therapies for the Treatment of COPD: A Network Meta-Analysis'' [1]. Network metaanalysis (NMA) is an important statistical technique, often used to make indirect treatment comparisons when no direct head-to-head studies are available [2].…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, another network metanalysis was released, on this occasion funded and led by GlaxoSmithKline 72 . The authors reported a favorable efficacy effect with fluticasone furoate triple therapy at 24 weeks in terms of lung function, annualized rate of moderatesevere exacerbations, health status and rescue medication use.…”
Section: Comparative Studiesmentioning
confidence: 99%